The Influence Of The Intensity Of Watching Korean Dramas On The Interest Of Teenagers In Changing Their Appearance - Aditya Dwi Saputra; Vethy Octaviani; Sri Narti (SENGKUNI Journal (Social Science and Humanities Studies), 2022)
The purpose of this researches is to find out the influence of watching Korean drama on teenagers’ interest in changing their styles. The purpose of this research is to find out if watching intensity can influence someone’s interest in changing styles. This research uses a quantitative with social approach. Data sources used in this research are 1) Primary data and 2) secondary data. Data are collected by using documents obtained from 1) library research, 2) field research. The result of this research shows that there are correlations and influences, the influence result is almost 80% means there is a close and significant relationship between intensity level with the will to change the style. This research result also shows that zero hypotheses (H0) are rejected and Hypothesis (Ha) is accepted means there is a correlation between intensity and correlation between someone’s will to change the styles. This research has practical implications that can help other researchers and can give pictures about the intensity of watching Korean Drama with interest in changing styles on teenagers.